Ecuaciones alométricas para predecir biomasa y carbono en la especie Vernonanthura patens (Kunth) H. Rob. “ocuera negra” en Pucallpa, Ucayali- Perú-2022 - Abensur Diaz, Giancarlos Israel (2025)
Given the diversity of forest species, more allometric equations are needed, especially for those in degraded areas of the Peruvian Amazon, such as Vernonanthura patens (“ocuera”). The objective was to determine the best allometric equation for quantifying biomass using Vernonanthura patens trees as the independent variable and biomass and carbon as the dependent variables. To achieve this, different mathematical models were analyzed, considering multiple factors that could influence the accuracy of the results. This will allow for the prediction of changes in biomass and stored carbon in its components. At least 36 individuals of Vernonanthura patens were randomly selected from three zones of the Institute for Amazonian Research in Pucallpa. Destructive sampling techniques were used, meaning the trees were felled to collect samples and field data. Regarding the equation, the best-fitting model was the simple quadratic nonlinear model, with an AIC of 143.34, BIC of 148.39, and an R² of 0.96. The resulting equation is as follows: BST = 1.5795864 - 0.71321 * D50 + 0.226922 * D50² (Equation 2). The predictor variables considered included diameter structures (D50, D100, D130), total height, and commercial height. The most representative regressor variable was D50, as it allowed biomass prediction for the species with 96% accuracy.